2004
DOI: 10.1038/nsmb734
|View full text |Cite
|
Sign up to set email alerts
|

The J domain–related cochaperone Tim16 is a constituent of the mitochondrial TIM23 preprotein translocase

Abstract: Mitochondria import the vast majority of their proteins from the cytosol. The mitochondrial import motor of the TIM23 translocase drives the translocation of precursor proteins across the outer and inner membrane in an ATP-dependent reaction. Tim44 at the inner face of the translocation pore recruits the chaperone mtHsp70, which binds the incoming precursor protein. This reaction is assisted by the cochaperones Tim14 and Mge1. We have identified a novel essential cochaperone, Tim16. It is related to J-domain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
153
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(169 citation statements)
references
References 45 publications
15
153
0
1
Order By: Relevance
“…In other cases, the Hsp70 and type III J-domain protein are recruited independently to the site of action, where the J-domain protein stimulates ATP hydrolysis by the partner Hsp70. This can be observed for the import machinery of mitochondria and chloroplasts (Westermann and Neupert, 1997;Becker et al, 2004;Kozany et al, 2004;Qbadou et al, 2007). The divergence of the C terminus among the type III J-domain proteins and their uniqueness suggests the possibility that they bind very different proteins.…”
Section: Discussionmentioning
confidence: 94%
“…In other cases, the Hsp70 and type III J-domain protein are recruited independently to the site of action, where the J-domain protein stimulates ATP hydrolysis by the partner Hsp70. This can be observed for the import machinery of mitochondria and chloroplasts (Westermann and Neupert, 1997;Becker et al, 2004;Kozany et al, 2004;Qbadou et al, 2007). The divergence of the C terminus among the type III J-domain proteins and their uniqueness suggests the possibility that they bind very different proteins.…”
Section: Discussionmentioning
confidence: 94%
“…However, beside the translocase-associated portion of the cochaperones Pam16 and Pam18, a significant non-translocase pool of the proteins has been found in mitochondria 11,26,30,31,35 . This, situation is now explained by the observed dynamics of the active translocase.…”
Section: Discussionmentioning
confidence: 99%
“…3b, the mutant form of Pam18 displays faster migration in SDS-polyacrylamide gel electrophoresis (SDS-PAGE) analyses and is efficiently recognized by the anti-Pam18 antiserum, lane 1 versus 2). Interestingly, despite the fact that Pam18 and Pam16 are considered to form a stable complex 11,16,26,31 , the inhibitory Pam16 remained translocase-associated in pam18-66 mitochondria. Thus, we concluded that the observed loss of motor function and concomitant instability of the translocation intermediate could be attributed to defective ATPase cycling at the import motor.…”
Section: Import Motor Activity Maintains a Tom/tim23 Intermediatementioning
confidence: 98%
See 2 more Smart Citations